(untitled) (Baghdad Science Journal, 2009)
A total of 722 algal taxa are recorded in Diyala River by different authors. Most of the identification algae belong to three Divisions: Bacillariophyceae (367, 50.8%), Chlorophyceae (179, 24.8%), and Cyanophyceae (126, 17.5%).